Development and validation of China’s Environmental Citizenship Questionnaire: evidence from junior high school students - Gao, Junhong; Jiang, Yong (Frontiers in Environmental Science, 2024)
The cultivation of environmental citizens has become an important measure to cope with the environmental crisis, and the research on the knowledge, conceptions, skills, attitudes, values, and actions of environmental citizens using the Environmental Citizenship Questionnaire (ECQ) is becoming a research focus. The research on environmental citizenship in China mainly staying at the level of theoretical research and descriptive research due to the accuracy of the ECQ. The emergence of the ECQ-China Version is helpful to promote the empirical research on environmental citizenship in China.This study verifies the effectiveness of the ECQ by removing 16 ECQ items which are not suitable for Chinese culture and evaluating environmental citizen-related knowledge among 550 Chinese junior high school students. The ECQ-China Version, consisting of 75 items, showed convincing results for all measurements: students’ past and present environmental citizenship behavior and the essential skills, values, attitudes, and competence that an environmental citizen should be equipped with had a significant impact on students’ future environmental citizenship behavior. This study suggests that: (1) Environmental citizenship education should not only focus on knowledge education, but also include skills education. (2) Environmental citizenship education should adhere to comprehensive principles, focusing on innovative practice of ideas and methods. (3) China’s environmental citizenship education should focus on the cultivation of citizens’ ability to participate, so that environmental citizenship can become the driving force for sustainable environmental development.